A influência do tempo de tela e dependência de internet sobre alterações metabólicas e o risco de diabetes em jovens do sexo masculino - Santos, Carolina Costa (2021)
With the technological expansion, children and young people spend more time in front of the television, computer, video game and cell phone. Dysfunctional internet use, or internet addiction (AI), has become a common behavioral addiction, with prevalence ranging from 1% to 14%. This has led the term screen time (ST), or exposure time to screen-based technology, to be incorporated into research in different areas. The increase in ST has a negative impact on physical and mental health, correlating with an increment in the prevalence of overweight, cardiometabolic risk factors and sleep disorders. The aim of this study was to evaluate internet dependence and excessive screen use and their association with the variables of metabolic syndrome (MS) and risk for type 2 diabetes mellitus (T2DM) in young male adults. 700 male candidates from 18 to 21 years old evaluated in the selection process for joining the Brazilian Air Force were invited to participate in the study. Among the 482 participants who signed the free and informed consent form, 378 answered the internet addiction test (IAT) and the Finnish Diabetes Risk Score (FINDRISC) questionnaire, electronically via Google forms, and all candidates underwent physical assessment,154 of them underwent laboratory tests and 128, bioelectrical impedance. Risk factors of MS were used for the dichotomous diagnosis and continuous risk score of MS (MetS z-score), which were correlated with internet dependence and ST, as well as with the risk score for T2DM. About 95% of participants reported ST longer than 3 hours, among them 39.6% spend more than 8 hours exposed to some type of screen. However, the score obtained in the IAT was less than 50 points in 92.2% of the cases, not allowing the characterization as internet dependence. Ten participants (6.4%) had 3 or more criteria for dichotomous MS diagnosis, in 72% of the studied sample, there was the presence of 1 or 2 criteria; only 21.4% were free of any metabolic feature. Continuous analysis of these criteria, using the MetS z-score, showed a high risk for MS, 0.25 ± 0.63 points, reflecting, on average, 58.3% risk for MS. The mean of MS criteria, and of MetS z-score, among individuals with less than 7 hours of sleep were higher than those with adequate sleep (p=0.036 and p=0.028, respectively). This reflected, on average, an increase of 0.24 points in the risk score for MS, compared to those with adequate sleep. We did not observe a direct impact of ST on the risk of MS and, despite the low risk according to FINDRISC score, staying more than 8 hours in front of some type of screen increased 1.22 points in the T2DM risk score. Although the excessive ST, we did not identify internet dependence, nor an association between ST and a higher risk of MS in healthy young males. Nonetheless, spending more than 8 hours in front of some type of screen resulted in an increase of 1,22 points in the T2DM risk score.